Science and Technology of Semiconductor-On-Insulator Structures and Devices Operating in a Harsh Environment Proceedings of the NATO Advanced Research Workshop on Science and Technology of Semiconductor-On-Insulator Structures and Devices Operating in a Harsh Environment, Kiev, Ukraine, 26-30 April 2004 - Flandre, Denis; Nazarov, Alexei N.; Hemment, Peter L.F (NATO Science Series II: Mathematics, Physics and Chemistry, Mathematics, Physics and Chemistry, 2005)
This proceedings volume archives the contributions of the speakers who attended the NATO Advanced Research Workshop on "Science and Technology of Semiconductor-On-Insulator Structures and Devices Operating in a Harsh Environment" held at the Sanatorium Puscha Ozerna, th th Kyiv, Ukraine, from 25 to 29 April 2004. The semiconductor industry has maintained a very rapid growth during the last three decades through impressive technological achievements which have resulted in products with higher performance and lower cost per function. After many years of development semiconductor-on-insulator materials have entered volume production and will increasingly be used by the manufacturing industry. The wider use of semiconductor (especially silicon) on insulator materials will not only enable the benefits of these materials to be further demonstrated but, also, will drive down the cost of substrates which, in turn, will stimulate the development of other novel devices and applications. In itself this trend will encourage the promotion of the skills and ideas generated by researchers in the Former Soviet Union and Eastern Europe and their incorporation in future collaborations.